2008
DOI: 10.1177/1046878108319867
|View full text |Cite
|
Sign up to set email alerts
|

A Systemic-Constructivist Approach to the Facilitation and Debriefing of Simulations and Games

Abstract: This article introduces some basic concepts of a systemic-constructivist perspective. These show that gaming simulation corresponds closely to a systemic-constructivist approach to learning and instruction. Some quality aspects of facilitating and debriefing simulation games are described from a systemic-constructivist point of view. Finally, a structure for debriefing, and some concrete examples of systemic-constructivist debriefing-methods are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
137
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(148 citation statements)
references
References 5 publications
3
137
0
8
Order By: Relevance
“…Topic guide. Based on the literature review in the previous sections, we identified eight phases that need to be addressed in a debriefing session of a research game, in which a large overlap exists with existing literature by Kriz (2010) and Peters and Vissers (2004). However, this paper recognizes the gap in the existing literature regarding the specific topics that need to be addressed within the validity and reliability analysis phase.…”
Section: Reliabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Topic guide. Based on the literature review in the previous sections, we identified eight phases that need to be addressed in a debriefing session of a research game, in which a large overlap exists with existing literature by Kriz (2010) and Peters and Vissers (2004). However, this paper recognizes the gap in the existing literature regarding the specific topics that need to be addressed within the validity and reliability analysis phase.…”
Section: Reliabilitymentioning
confidence: 99%
“…For a more in-depth look at how we applied part of this framework in specific cases in the Dutch railway sector, we refer to Van den Hoogen et al (2014a). The framework incorporates existing notions from the literature (Peters & Vissers, 2004;Kriz, 2010) and adds a more thorough operationalization of validity and a methodology by which to actually study validity in the debriefing. The table also shows the ideal roles of each participant.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…As described in the literature on debriefing gaming simulations, after every participatory event the researchers should create an opportunity for participants to express their feelings about this event (Kriz 2008). This typically takes the form of an open-group discussion about what happened during a participatory event, prompted by questions such as: "how did you feel during the session?," "do you wish to express some specific messages to your fellow participants?," or "when did you not feel at ease and why?".…”
mentioning
confidence: 99%
“…In addition to the value of the use of the theory of constructivism for gaming design purposes, instruction with games central to pedagogical practices resulted in higher levels of learning [6], [12], [14]- [20]. Researchers noted that instructional games, when supported by instructional practices using constructivism, netted increased learning across multiple instructional settings, including nursing, social studies, and science.…”
Section: B Gaming and Constructivismmentioning
confidence: 99%